2017
DOI: 10.4103/jips.jips_290_16
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to correlate between clinically and radiographically determined sagittal condylar guidance in participants with different skeletal relationships

Abstract: Context:Many authors have conducted studies that determine horizontal condylar guidance (HCG) using various methods, articulator systems, and recording materials. However, there is a dearth of literature on variability existing in HCG in individuals with different skeletal relationships. This study is an attempt to verify whether such a difference exists or not.Aims:The aim of this study is to determine and correlate the HCG in individuals with Angle's Class I, Class II, and Class III malocclusion using radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
(46 reference statements)
0
15
0
1
Order By: Relevance
“…advocated for clinical method as radiographic method yielded a consistent greater value as compared to clinical method. [32] Clinical protrusive method for each individual is mandatory to determine accurate HCG values. Cephalometric tracing of diagnostic radiographs can delineate an idea about HCG angle before any clinical step, which will help the operator to choose the type of articulator and select posterior teeth.…”
Section: Discussionmentioning
confidence: 99%
“…advocated for clinical method as radiographic method yielded a consistent greater value as compared to clinical method. [32] Clinical protrusive method for each individual is mandatory to determine accurate HCG values. Cephalometric tracing of diagnostic radiographs can delineate an idea about HCG angle before any clinical step, which will help the operator to choose the type of articulator and select posterior teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Both Katsavrias et al [ 2 ], investigating digitized tomograms, and Akahane et al [ 31 ], investigating dry skulls, found a smaller eminence to FH angle in the Class III group. Singh et al [ 6 ] traced AEI with one clinical method and two radiographic methods on lateral cephalograms. One of the radiographic methods, the tangent method [ 6 ] is comparable to our method and showed that the Class III group had a significantly lower angle (37.60°) compared to Class I (41.90°) and Class II (43.90°).…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al [ 6 ] traced AEI with one clinical method and two radiographic methods on lateral cephalograms. One of the radiographic methods, the tangent method [ 6 ] is comparable to our method and showed that the Class III group had a significantly lower angle (37.60°) compared to Class I (41.90°) and Class II (43.90°). These results seem to be opposite to those of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All included studies were unicentric trials published between 2011 and 2020. Typically, 26 studies were conducted in India, 1,7,11,13,14,19,20,[23][24][25][26][27]29,30,32,[34][35][36][37][38][39][40][41][42][43][44] two each in Iran 8,28 and Saudi Arabia 22,33 and one each in Nepal, 21 Korea 31 and Poland. 9 In total, 20 studies included were conducted among dentate patients having a total sample size of 595 and age ranged from 18-43 years 1,19,20,21,25,27,30,32,34,[37][38][39][40]42,44 while 15 studies included were conducted among edentulous patients having a total sample size of 277 and age ranged from 35-75 years.…”
Section: Study Characteristicsmentioning
confidence: 99%